On the capacity and scheduling of a multi-sector cell with co-channel interference knowledge - Mitran, Patrick. (2011)
We study the capacity of a single-hop wireless cell comprised of M fixed directional antennas concentrically arranged around a common axis and each reusing the same channel. The premise for this architecture is that co-channel interference between the fixed directional beams can be identified and reported, allowing joint conflict-free scheduling, i.e., it becomes possible to compute the schedule over all the M sectors together. We are primarily interested in studying the capacity gains that can be realized as a function of the number of sectors, the parameters of the directional antennas and other system parameters. Our analytical and numerical results yield several useful engineering insights on the selection of antenna parameters, the impact of node placement, and the impact of physical layer parameters. This study demonstrates how Space Division Multiple Access (SDMA) can yield excellent capacity provided inter-cell co-channel coexistence is achieved. Such coexistence techniques are now being considered for cognitive radio TV White Space systems and by evolving standards such as the IEEE 802.16h.